PHYSICAL QUALITY AND NUTRIENT CONTENT OF BROILER RATION ADDITED WITH DUCKWEED FERMENTED WITH Saccharomyces cerevisiae - I N. S., Govinda; Suryani, N. N.; Mariani, N. P. (Jurnal Peternakan Tropika, 2024)
This study investigates the physical properties and nutrient content of rations added with fermented duckweed using Saccharomyces cerevisiae. The commercial ration used is Br-2 from PT.Wonokoyo, and duckweed was taken from nature. A compeletely randomized design with  four treatments and four replications was used for physical quality and calculation methods on nutrient content, consisting of R0 100% ration, R1 95% ration + 5% fermented duckweed, R2 90% ration + 10% fermented duckweed and R3 85% ration + 15% fermented duckweed. The variables observed included physical quality and nutrient content. The results showed that on the ration physical quality, 5-15% substitution reduced (P<0.05) the density by 521.01-476.06g/l and increased (P<0.05) the water absorption capacity by 2.02- 2.24% compared to the ration without the addition of duckweed which had a density of 554.37g/l and a water absorption capacity of 1.78%, while the water solubility of all treatments showed no significant different values (P> 0.05), i.e. each of 17.24%, 17.27%, 16.17% and 19.76%. Nutrient content increased except for the OM. The conclusion from this study the addition of duckweed can reduce density, increase absorption, has no effect on water solubility, increases DM, ash, CP and CF but decreases OM of the ration.